The adult learner the definitive classic in adult education and human resource development - Knowles, Malcolm S. (Malcolm Shepherd) 1913-1997; Holton, Elwood F. 1957-; Swanson, Richard A. 1942- (Elsevier, 2005)
"The Adult Learner, Sixth Edition is essential reading for adult learning practitioners, students and HRD professionals. It provides a theoretical framework for understanding the adult learning issues both in the teaching and workplace environments."--BOOK JACKET.